2018
DOI: 10.1681/asn.2017111155
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-Sensing Receptor Increases Activity of the Renal NCC through the WNK4-SPAK Pathway

Abstract: Hypercalciuria can result from activation of the basolateral calcium-sensing receptor (CaSR), which in the thick ascending limb of Henle's loop controls Ca excretion and NaCl reabsorption in response to extracellular Ca However, the function of CaSR in the regulation of NaCl reabsorption in the distal convoluted tubule (DCT) is unknown. We hypothesized that CaSR in this location is involved in activating the thiazide-sensitive NaCl cotransporter (NCC) to prevent NaCl loss. We used a combination of and models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 72 publications
(100 reference statements)
1
38
0
Order By: Relevance
“…In the present study, we have demonstrated that knockout animals have exaggerated calcium wasting in response to acute furosemide treatment. Bazua‐Valenti et al recently proposed that increased calcium delivery to the DCT, as occurs following furosemide treatment, stimulates the apical calcium‐sensing receptor (CsR) to activate WNK4 and NCC, further promoting hypercalciuria (Bazúa‐Valenti et al ). However, we found increased hypercalciuria following acute furosemide administration in the absence of WNK4, which is the opposite of which this mechanism would indicate.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have demonstrated that knockout animals have exaggerated calcium wasting in response to acute furosemide treatment. Bazua‐Valenti et al recently proposed that increased calcium delivery to the DCT, as occurs following furosemide treatment, stimulates the apical calcium‐sensing receptor (CsR) to activate WNK4 and NCC, further promoting hypercalciuria (Bazúa‐Valenti et al ). However, we found increased hypercalciuria following acute furosemide administration in the absence of WNK4, which is the opposite of which this mechanism would indicate.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to TAL, where CaSR signaling inhibits the NaCl reabsorption, activation of CaSR in DCT cells has been suggested to stimulate NCC in order to compensate for NaCl loss in the preceding TAL [13]. CaSR-induced NCC activation is mediated by WNK4, at least in cell culture and Xenopus laevis oocytes transfected with the two products [13].…”
Section: Casr Function In Dctmentioning
confidence: 99%
“…In contrast to TAL, where CaSR signaling inhibits the NaCl reabsorption, activation of CaSR in DCT cells has been suggested to stimulate NCC in order to compensate for NaCl loss in the preceding TAL [13]. CaSR-induced NCC activation is mediated by WNK4, at least in cell culture and Xenopus laevis oocytes transfected with the two products [13]. In these ex vivo systems, CaSR activation has been shown to promote PKC-dependent phosphorylation of WNK4 and KLHL3 resulting in enhanced WNK4 kinase activity and reduced degradation of the kinase via the KLHL3-dependent pathway [13,91].…”
Section: Casr Function In Dctmentioning
confidence: 99%
See 2 more Smart Citations